Management of patient with necrotizing fasciitis: a challenge for anaesthesiologist - Mahajan, Reena; Malhotra, Suchitra (International Journal of Research in Medical Sciences, 2017)
Necrotising fasciitis, a highly lethal infection of deep seated subcutaneous tissue and fascia, is associated with high mortality and long term morbidity. A five year old child of necrotizing fasciitis with poor general condition, deranged investigations and unstable vitals was posted for debridement. After initial resuscitation, TIVA was given, intraoperative period was uneventful and post operatively patient was shifted to recovery room as fully conscious with O2 by face mask. After 1½ hours, patient became drowsy, hypotensive with bradycardia and urine output was nil. Immediate resuscitation started and vasopressors added. Despite all aggressive interventions, the patient died due to sepsis induced multiorgan failure. Blood samples and wound aspirate culture showed group A beta hemolytic Streptococcous. In this case report we discuss the best possible management of such patients and tried to minimize several barriers like lack of early recognition of severe sepsis and septic shock, treatment delay, lack of several investigations and drugs, shortage of health care providers, absence of locally written protocol, remote area and tried to give the massage that adherence to published guidelines for the management of severe sepsis patients lowers mortality.